Analisa Indeks Keandalan pada Pembangkit Listrik Tenaga Mesin Gas (PLTMG) MPP Flores - Kapu, Joannes Mario Graciano; Jasa, Lie; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 23 No 1 (2024): (Januari - Juni ) Majalah Ilmiah Teknologi Elektro, 2024)
Electrical energy is a vital need that is increasing from year to year. As a need, the provision of electricity needed by consumers needs to be considered so that electrical energy can be distributed reliably, safely and environmentally friendly and in accordance with established standards. To measure the ability of the generator to meet electricity needs, a reliability index is needed. This study aims to assess the reliability index at the Flores MPP Gas Engine Power Plant (PLTMG). The LOLP (Loss Of Load Probability) index value is used to perform calculations. In this study, in finding the reliability index of a generation system, referring to SPLN: 68-1A: 1986, that is for the Java-Bali system it is 3 days/year and for systems outside Java-Bali it is 3.5-5 days/year. Based on the research results, the LOLP value of the Flores MPP PLTMG in 2022 is 4.5295 days/year and based on SPLN: 68-1A: 1986, therefore the Loss Of Load Probability (LOLP) value at the Flores MPP PLTMG is said to be reliable because it meets the standards.